Current concepts in the techniques, indications and outcomes of meniscal repairs. - Karia,M; Ghaly,Y; Al-Hadithy,N; Mordecai,S; Gupte,C (Eur J Orthop Surg Traumatol, 2019)
Knee arthroscopy for meniscal tears is one of the most commonly performed orthopaedic procedures. In recent years, there has been an increasing incidence of meniscal repairs, as there are concerns that meniscectomy predisposes patients to early osteoarthritis. Indications for meniscal repair are increasing and can now be performed in older patients who are active, even if the tear is in the avascular zone. Options for meniscal tear management broadly fall into three categories: non-operative management, meniscal repair or meniscectomy. With limited evidence directly comparing each of these options optimal management strategies can be difficult. Decision making requires thorough assessment of patient factors (e.g. age and comorbidities) and tear characteristics (e.g. location and reducibility). The purpose of this paper is, therefore, to review the management options of meniscal tears and summarize the evidence for meniscal tear repair.